High-Commitment Leadership:: A Study of Iranian Executives - Dastmalchian, Ali; Javidan, Mansour (Journal of Comparative International Management)

(untitled) (Management Futures, 1998)
This study tests Conger-Kanungo hypothesis that employee empowerment can help build a strong positive attitude among subordinates. The findings on Iranian executives and managers point to the conclusion that encouraging employee participation, setting motivational goals, removing bureaucratic barriers and rewarding performance lead towards building a loyal workforce.